The quality of the KombiFiD-sample of enterprises from manufacturing industries: Evidence from a replication study - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
This study tests whether the KombiFiD sample can be regarded as a high quality data set for empirical research on enterprises from manufacturing industries. It performs an empirical investigation using the original data in a first step and replicates exactly this investigation using the KombiFiD sample in a second step. For West Germany a comparison of the results based the original data and on the KombiFiD sample points to by and large highly similar results. Contrary to this the big picture is not in favour of the quality of the KombiFiD sample for East Germany where the KombiFiD sample is too small and differences between the results based on this sample and the original data are too large to suggest the use of the KombiFiD data in empirical investigations.
Keywords: C81; 330; KombiFiD; firm level data; Germany; Verarbeitendes Gewerbe; Statistik der Unternehmen und Arbeitsstätten; Stichprobenverfahren; Deutschland